The role of daily physical activity in preventing low back pain - Opara, Józef; Polak, Anna (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Low back pain (LBP) is a common disease in developed countries that places a substantial ﬁnancial burden on healthcare sys-tems. As many as 60–80% of the US population suﬀers from LBP over their lifetime, and although symptoms usually disappear within a few weeks of onset, their recurrence rate is high. In recent years, its signiﬁcance to human health has gained increasing attention from the World Health Organization (WHO). LBP prevention guidelines recommend physical activity as one of the key countermeasures, with evidence indicating that it is crucial for primary and secondary prevention. According to many authors, combining moderate-intensity exercise and education programmes should be the ﬁrst-line approach to preventing LBP. The current work provides a narrative review of physical activity in LBP prevention, outlines its role in protecting people from the occur-rence (primary prevention) and recurrence (secondary prevention) of LBP symptoms, and suggests future research directions.
Keywords: low back pain; prevention; physical activity; treatment